2009
DOI: 10.1007/s11575-009-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

How Firm Performance Affects Internationalization

Abstract: 0Only a few studies have investigated whether a firm's performance has an effect on its internationalization. These studies, focusing on actual firm performance, have suggested a resource-based argument and generally found non-significant results. 0In this paper, we argue that relative firm performance is critical in determining a firm's internationalization because it influences a firm's attitude toward risk-taking. We apply prospect theory to predict this relationship. 0Using time-series, cross-sectional ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 74 publications
7
48
2
1
Order By: Relevance
“…Thus, they have extra fresh money to support their international activity. This finding also supports Jung & Bansal (2009) on how performance affects companies' internationalization. But it still requires further research to prove those performance effects in Indonesia manufacturing companies.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, they have extra fresh money to support their international activity. This finding also supports Jung & Bansal (2009) on how performance affects companies' internationalization. But it still requires further research to prove those performance effects in Indonesia manufacturing companies.…”
Section: Methodssupporting
confidence: 77%
“…On the other hand, performance can also affect companies' internationalization. Jung & Bansal (2009) argued that performance affects internationalization in two ways. First, performance takes the role of a benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on similar firms from Japan, Jung and Bansal (2009) found an inverted u-shape relationship between change in the degree of internationalization and performance relative to the historical aspiration level while for performance relative to the social aspiration level the relationship was monotonically positive. Next to these notable discrepancies, studies on performance feedback have often shown that sometimes performance relative to the historical aspiration level has an impact on adaptation while performance relative to the social aspiration level does not or vice versa (Chen & Miller, 2007;Greve, 2003c;Iyer & Miller, 2008).…”
Section: Performance Feedback and Firm Level Change In Randd Investmentmentioning
confidence: 96%
“…In some studies, a U-form relationship is clearly identified (Thomas 2006;Ruigrok & Wagner 2003). Conversely Brock et al (2006) and Jung and Bansal (2009) find an inverse U-form connection, while Lu and Beamish (2004), Thomas and Eden (2004), Ruigrok et al (2007) and Vilas-Boas and Suàrez-Gonzàlez (2007) detect an S-form link. In addition, Contractor (2007) suggests a three-stage model where U, inverted-U and linear relationships depend on the degree of internationalisation.…”
Section: The Conflicting Relationship Between Internationalisation Anmentioning
confidence: 99%